2013
DOI: 10.2174/13816128113199990387
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Complications of Anderson-Fabry Disease

Abstract: Characteristic clinical manifestations of AFD such as acroparesthesias, angiokeratoma, corneal opacity, hypo/ and anhidrosis, gastrointestinal symptoms, renal and cardiac dysfunctions can occur in male and female patients, although heterozygous females with AFD usually seem to be less severely affected. The most prominent CNS manifestations consist of cerebrovascular events such as transient ischaemic attacks (TIAs) and (recurrent) strokes. For the most part, CNS complications in AFD have been attributed to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 67 publications
(80 reference statements)
0
49
0
5
Order By: Relevance
“…Increasing studies have revealed that chronic hyperglycemia and hyperlipidemia is a major trigger factor for the initiation and development of diabetes-induced cognitive deficits 6,7. In addition, disorder of carbohydrate, lipid, and protein metabolism under diabetic circumstances can cause amyloid β (Aβ) deposition, abnormal insulin signaling, and severe inflammatory response, which also contribute to diabetes-induced neuronal damage and cognitive deficits 810. Therefore, amelioration of hyperglycemia and hyperlipidemia and alternation of abnormal insulin signaling may be beneficial for the treatment of cognitive deficits induced by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have revealed that chronic hyperglycemia and hyperlipidemia is a major trigger factor for the initiation and development of diabetes-induced cognitive deficits 6,7. In addition, disorder of carbohydrate, lipid, and protein metabolism under diabetic circumstances can cause amyloid β (Aβ) deposition, abnormal insulin signaling, and severe inflammatory response, which also contribute to diabetes-induced neuronal damage and cognitive deficits 810. Therefore, amelioration of hyperglycemia and hyperlipidemia and alternation of abnormal insulin signaling may be beneficial for the treatment of cognitive deficits induced by diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…We surprisingly found that, in spite of what is known for myocardial, neuropathic, or renal complications, age is a stronger determinant than gender for pituitary size [1,14,15]. This is not explained by gender imbalance in older FD.…”
Section: Discussionmentioning
confidence: 56%
“…Progressive deposition of Gb3 in these organ systems leads to renal and heart failure, as well as debilitating pain as a result of nervous system involvement [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Major morbidity in Fabry disease is due to renal involvement, which can vary from asymptomatic proteinuria to progressive renal failure; cardiovascular disease including syncope, cardiomyopathy, valvular heart disease, and ischemic heart disease [1]; central nervous system involvement such as dizziness, memory impairment, depression, and stroke [2]; and psychiatric manifestations such as depression and insomnia.…”
Section: Discussionmentioning
confidence: 99%